METHOD OF OBSERVATION AND THEIR EFFECTS IN THE SELECTION OF POTENTIAL FOOTBALL GOALKEEPERS - Zerf, Mohammed; Besultan, Hadje; Attouti, Norddine; Touati, Blidi; Mokkedes, Moulay Idriss (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2017)
The criteria and methods for goalkeeper selection are more strict and complex than those of field players. Founded on its principles, the present study tried to examine the strengths and weaknesses of selection process practised by Algerian coaches. Interpret by Algerian scientists in their subjectivity in evaluating the amount of body fat and its effect on physical performance. Seen it's built with the naked eye. Confirmed by FIFA in two categories normal vs overweight, they should work harder under these conditions. For this proposal, eight teams from the leagues of Oran, Algeria Championship second division were involved in the study. Their goalkeepers were classified into the following groups: total (GK = 28), Main goalkeeper (MG = 14) and replacement goalkeeper (RG = 14).Tested at the end of the outward phase by penalty kicks test, 'T' Drill Test, Ruler Drop Test (TR) and anthropometric parameters (BH, BMI, BFP, BW). Backed on the applied statistical where our total sample is categorised in overweight, as well as no statistically significant differences between the two groups in all the comparisons practised. Our results confirm the weaknesses of traditional methods. Admit by similar studies in their subjective in evaluating the amount of body fat and its effect on physical performance correlate to anthropometric measurement.
Keywords: observation method, selection procedure, potential goalkeeper, Algerian soccer game.